Landscape and Perception: A systematic review - Hanieh Jafari Khaledi; Mehdi Khakzand; Mohsen Faizi (Landscape Online, 2022)
Accurate knowledge of human perception can help designers to create desirable spaces. An increase in publications from 2000 to 2020 demonstrates that studies in human perception of the landscape are evolving. This systematic review aims to comprehensively review existing knowledge and published papers on human perception concerning landscape to promote these approaches in this field for future research. Therefore, a systematic literature search analysis of 255 articles was drawn from four databases: Scopus, ScienceDirect (Elsevier), SAGE, and Taylor & Francis. Results show that the previous concerns are categorized into four main categories: human, heritage, infrastructure, and landscape characteristics. The results of this paper suggest that in future studies researchers should study the heritage and infrastructures factors and evaluate the potential and effects of these issues in the process of human-environmental interactions.